Lactic acid bacteria and identification with PCR-DGGE - BİÇER, Yusuf; UÇAR, Gürkan (International Journal of Biological Research, 2017)
Lactic acid bacteria (LAB) are an important group in the industrially using microorganisms. The first pure cultures of bacteria was "Bacterium lactis" (probably Lactococcus lactis), obtained in 1873 by J. Lister. LAB are Gram-positive, non motile, non spore-forming, except Sporolactobacillus inulinus, catalase negative, microaerophilic or anaerobic microorganisms. LAB can be found in milk and dairy products, plants and human and animal intestinal mucosa. LAB have low Guanine and Cytosine (G+C) ratio.The industrial applications of lactic acid bacteria is considered, it is emphasized that reliable typing methods in strain levels are getting important about both study on cultures used in functional foods and determining the performance of LAB starter cultures. Denaturing Gradient Gel Electrophoresis (DGGE) is the most common technique in molecular fingerprinting culture-independent techniques. The technique is based on the separation of the same length but having different sequences of the Polymerase Chain Reaction (PCR) products.